The Influence Of Online Registration Application Implementation And Waiting Time On Patient Satisfaction Through Health Worker Performance As A Mediating Variable At Rsud Ibnu Sina Gresik - Milyantono, Riyan Charlie; Yuliaty, Farida; Rulia (LP2M IAIN Palopo, 2026)
This study aims to analyze the influence of online registration application implementation and service waiting time on patient satisfaction through health worker performance as a mediating variable at RSUD Ibnu Sina Gresik. The research method used is quantitative with descriptive and verificative approaches. Data collection was carried out by distributing questionnaires to 100 outpatient respondents. The data analysis techniques utilized Path Analysis and the Sobel Test. The results showed that: (1) online registration application had a positive and significant effect on health worker performance (β = 0.259; t = 2.522; sig. = 0.013); (2) waiting time had no significant partial effect on health worker performance (β = 0.174; t = 1.696; sig. = 0.093); (3) both variables simultaneously influenced health worker performance (F = 7.409; sig. = 0.001; R² = 13.3%); (4) health worker performance significantly influenced patient satisfaction (β = 0.545; t = 6.439; sig. = 0.000; R² = 29.7%); (5) health worker performance fully mediated the relationship between application and patient satisfaction (Sobel Z = 2.348; p = 0.019); and (6) health worker performance did not mediate the influence of waiting time on patient satisfaction (Sobel Z = 1.640; p = 0.101). This study concludes that optimizing registration technology effectively supports staff performance, which directly impacts patient satisfaction.